2009
DOI: 10.1103/physrevb.79.094110
|View full text |Cite
|
Sign up to set email alerts
|

Phase field simulations of coupled phase transformations in ferroelastic-ferroelastic nanocomposites

Abstract: We use phase-field simulations to study composites made of two different ferroelastics (e.g. two types of martensite). The deformation of one material due to a phase transformation can elastically affect the other constituent and induce it to transform as well. We show that the phase transformation can then occur above its normal critical temperature, and even higher above this temperature in nanocomposites than in bulk composites. Microstructures depend on temperature, on the thickness of the layers, and on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…A separate study in NiTi, revealed that grains under 50 nm in diameter did not transform [15]. In contrast, increasing grain constraints have been shown to increase the complexity of martensite variants [16], and could lead to unique martensitic structures such as dot-like domains [17]. While recent dynamic TEM [18] and pulsed X-ray experiments [19] are providing information about the transformation with unprecedented resolution current experimental techniques lack the ability to characterize the nucleation and propagation of transformations in ultra-fine SMAs and significant questions remain unanswered.…”
Section: Introductionmentioning
confidence: 90%
“…A separate study in NiTi, revealed that grains under 50 nm in diameter did not transform [15]. In contrast, increasing grain constraints have been shown to increase the complexity of martensite variants [16], and could lead to unique martensitic structures such as dot-like domains [17]. While recent dynamic TEM [18] and pulsed X-ray experiments [19] are providing information about the transformation with unprecedented resolution current experimental techniques lack the ability to characterize the nucleation and propagation of transformations in ultra-fine SMAs and significant questions remain unanswered.…”
Section: Introductionmentioning
confidence: 90%
“…Analogous chessboard patterns have been observed and reproduced by PF in connection with diffusive alloy decomposition [22]. For displacive transformations, these ubiquitous structures [20] have also been obtained in two-dimensional PF calculations: very unstable, they are stabilized in small samples, but decay into more conventional laminatelike structures at large sizes [23]. We make here a first exploration of this physically important effect in three dimensions (3D) using PF-RP for an imposed deformation F(t) with α = 0.3.…”
mentioning
confidence: 52%
“…The weak formulation of Eqs. (26.1)-(26.3) and (27) are derived by multiplying the equations with weighing functions {Φ, U U U, Σ Σ Σ, Θ} and transforming them by using the integration by parts. Let X denote both the trial solution and weighting function spaces, which are assumed to be identical.…”
Section: Weak Formulationmentioning
confidence: 99%